A Silicon-Embedded Inductor Surrounded by Porous Silicon for Improved Quality Factor. (9th June 2018) - Wu, Rongxiang; Liao, Niteng; Sin, Johnny K. O.; Bardet, Benjamin; Billoué, Jérôme; Gautier, Gaël
Abstract : A Backside Silicon-Embedded Inductor (BSEI) surrounded by porous silicon (PS) is reported for quality factor (Q) improvement. Successful formation of a conformal PS layer surrounding deep trenches (where the inductor coil is accommodated) is demonstrated. Experimental results show that although the DC resistance of the BSEI surrounded by PS is 73% higher than the conventional BSEI due to the non-optimized process, a 24% improvement in the peak Q and an 86% increase in the peak Q frequency can be achieved.